2022
DOI: 10.1186/s41983-021-00441-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical implication of adverse childhood experiences and their association with substance use disorder among patients with schizophrenia

Abstract: Background Adverse childhood experiences (ACEs) and substance use disorder (SUD) are well-known risk factors for psychosis and dramatically affect schizophrenia. In this research, we aimed to measure the prevalence of adverse childhood experiences and substance use disorder in patients with schizophrenia and assess the effect of ACEs on the clinical presentation and overall functioning and the association between them and SUD in patients with schizophrenia. A cross-sectional study included a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that nutrient pan is low among self-stigmatized individuals (Clari et al, 2022;Díaz-Cutraro et al, 2022). Discussion of previous research on self-stigma which affects the quality of physical and psychological health of schizophrenic patients which is reflected in the patient's ability to maintain the body and coping abilities against perceived stressors (Cai et al, 2022;Yosep et al, 2022;Yousef et al, 2022). Schizophrenia with a negative self-stigma raises low expectations, resulting in low self-esteem and self-ability so that it is directly related to the recovery process in the form of decreased awareness or self-view of the disease which in turn greatly impacts the quality of life of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nutrient pan is low among self-stigmatized individuals (Clari et al, 2022;Díaz-Cutraro et al, 2022). Discussion of previous research on self-stigma which affects the quality of physical and psychological health of schizophrenic patients which is reflected in the patient's ability to maintain the body and coping abilities against perceived stressors (Cai et al, 2022;Yosep et al, 2022;Yousef et al, 2022). Schizophrenia with a negative self-stigma raises low expectations, resulting in low self-esteem and self-ability so that it is directly related to the recovery process in the form of decreased awareness or self-view of the disease which in turn greatly impacts the quality of life of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…These ACEs encompass occurrences involving physical, psychological, and sexual abuse, as well as physical and mental neglect, and dysfunction within the family ( 3 ). Individuals with schizophrenia as well as those with other non-psychiatric diseases with severe ACEs, displayed higher levels of comorbidity, necessitated increased medication usage, and required the involvement of a care coordinator compared to individuals with moderate or no ACEs ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…This implies a dose-response connection, where the risk of adverse effects on physical and mental health exponentially rises with additional ACEs ( 33 , 35 ). Individuals with schizophrenia who had multiple ACEs histories exhibited more severe symptoms and unfavorable clinical results ( 4 , 36 38 ). Those with higher levels of ACEs tended to have lower levels of social support, which exhibited a positive correlation with suicide in individuals with schizophrenia, and decreased coping abilities ( 39 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood maltreatment increases the likelihood of later-life neuropsychiatric disorders, such as anxiety, schizophrenia, and substance use disorders [1][2][3]. Cognitive dysfunction is a central feature of these disorders [4][5][6][7][8][9][10]. Additionally, early life adversity (ELA) affects brain regions important for cognition, such as the prefrontal cortex (PFC) and hippocampus, which in turn influences cognitive development [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%